2017
DOI: 10.1136/annrheumdis-2017-212189
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cardiac rhythm disturbances and aortic regurgitation in different spondyloarthritis subtypes in comparison with general population: a register-based study from Sweden

Abstract: Patients with SpA are at increased risk of aortic regurgitation, cardiac rhythm disturbances and, as a probable consequence, also PM. Particularly for AF, the most common arrhythmia, increased caution is warranted, whereas AV block should be looked for especially in men with AS or uSpA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 38 publications
7
47
2
Order By: Relevance
“…[4][5][6] However, as for heart comorbidities, valvular heart disease was not mentioned in the ASAS-COMOSPA study, while it has been reported to be associated with SpA in a number of recent studies, based both on epidemiology and pathology. [7][8][9] As for risk factors for cardiovascular diseases, hyperuricaemia was not included as well, while uric acid has also been proven to be related to cardiovascular disease in the recent years. [10][11][12][13] Since there are still some comorbidities and risk factors to be evaluated, we proposed a research to include valvular heart disease as a comorbidity of SpA and hyperuricaemia as a risk factor of cardiovascular disease among patients with SpA.…”
mentioning
confidence: 99%
“…[4][5][6] However, as for heart comorbidities, valvular heart disease was not mentioned in the ASAS-COMOSPA study, while it has been reported to be associated with SpA in a number of recent studies, based both on epidemiology and pathology. [7][8][9] As for risk factors for cardiovascular diseases, hyperuricaemia was not included as well, while uric acid has also been proven to be related to cardiovascular disease in the recent years. [10][11][12][13] Since there are still some comorbidities and risk factors to be evaluated, we proposed a research to include valvular heart disease as a comorbidity of SpA and hyperuricaemia as a risk factor of cardiovascular disease among patients with SpA.…”
mentioning
confidence: 99%
“…Patients with AS have a twofold increased risk in second/third‐degree atrioventricular block and pacemaker implantation compared with the general population . Furthermore, male patients are more likely to have conduction disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Ankylosing spondylitis (AS) increases the risk of various cardiac manifestations, specifically conduction disturbances, aortic regurgitation, and coronary artery disease . Although the prevalence of conduction disturbances ranges from 5% to 33%, complete atrioventricular block is quite rare .…”
Section: Introductionmentioning
confidence: 99%
“…A few large register-based studies, all lacking individual AS characteristics of the included patients, show an increased risk of aortic valve disease, atrioventricular block (AVB) and pacemaker implantation in patients with AS compared with the general population 4 8 9. Else, the majority of previous studies of conduction disturbances or aortic regurgitation in AS are cross-sectional or historical cohort studies 3 10–19.…”
Section: Introductionmentioning
confidence: 99%